Integrative Land-Biodiversity-Climate Action: Leveraging Synergies through Ecosystem Restoration in Uzbekistan - Mirzabaev, Alisher; Akramkhanov, Akmal (The Economics of Land Degradation (ELD) Initiative, 2025)
The English version of the Uzbekistan country case study, detailing methodological steps, cost-benefit estimations, institutional coordination needs, and national alignment with Rio Convention targets. It spatially identifies 1.37 million hectares suitable for restoration and outlines mechanisms to enhance national coherence and financing efficiency.